Analisis Peningkatan Sikap dan Minat Wirausaha Mahasiswa melalui Penerapan Project Based Learning Bermuatan Technopreneurship - Siti Nafilah; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This research aims to find out whether or not the attitude and interest of students in industrial electrical installation courses through the application of project-based learning charged with technopreneurship.In addition, to find out the attitude and entrepreneurial interests of students after applying project-based learning loaded with technopreneurship.In addition, to find out the improvement between the attitude and interest of student entrepreneurs before applying project-based learning loaded technopreneurship and attitudes and interests of student entrepreneurs after the implementation of project based learning loaded technopreneurship at Padang State University. This research uses quantitative approaches with research methods. The instrument used is a response to the attitude and entrepreneurial interest of students towards PJBL. The subjects in this study were D4 students who took industrial electrical installation courses including grades 3TEIB1 and 3TEIB2 numbering 30 people. Analysis of instrument data in this study using the help of the SPSS 25.0.0 program. and Microsoft excel. The results of this study show that: Student entrepreneurial attitude towards the application of project-based learning loaded technopreneurship that has been applied is emerging, and effective to improve the entrepreneurial attitude of students from the results of research that shows in the moderate category. Student entrepreneurial interest in the application of project-based learning loaded with technopreneurship that has been applied is also emerging and is very effective to increase student entrepreneurial interest from research results that show in the high category.